1982
DOI: 10.1063/1.331217
|View full text |Cite|
|
Sign up to set email alerts
|

Temperature profiles induced by a scanning cw laser beam

Abstract: Articles you may be interested inTemperature rise induced by a cw laser beam revisited J. Appl. Phys. 57, 5123 (1985); 10.1063/1.335245 Nonlinear calculation of a temperature profile produced in a twolayer structure by a scanning cw elliptical laser or electron beam J. Appl. Phys. 57, 965 (1985); 10.1063/1.334698 Erratum: Temperature profiles induced by a scanning cw laser beam [J. Appl. Phys. 5 3, 4364 (1982)] J.Temperature evolutions in silicon induced by a scanned cw laser, pulsed laser, or an electron beam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

1984
1984
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(29 citation statements)
references
References 5 publications
0
27
0
1
Order By: Relevance
“…Their results showed that with prior knowledge of the thermal conductivity, accurate temperature can be calculated and are valid for any material. Moody and Handel [5] as well used a continuous wave (CW) elliptical laser beam using an improved formalism of the Kirchhoff transformation to evaluate the temperature profiles on a silicon substrate. Thermal conductivity, diffusivity, and the surface reflection were considered as important functions in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that with prior knowledge of the thermal conductivity, accurate temperature can be calculated and are valid for any material. Moody and Handel [5] as well used a continuous wave (CW) elliptical laser beam using an improved formalism of the Kirchhoff transformation to evaluate the temperature profiles on a silicon substrate. Thermal conductivity, diffusivity, and the surface reflection were considered as important functions in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For most materials, the thermally-induced reflectance change actually results from thermally-induced absorption coefficient change. According to [26], the reflectance of Si thin film is a function of temperature. The reflectivity change can be expressed as where T m is the initial melting temperature, T f is the boiling point temperature, and R(T) is the reflectivity.…”
Section: Read-only Super-resolution Optical Disks With Thermally Indumentioning
confidence: 99%
“…Nissim et al [10] presented an analy-tical solution for a moving elliptical Gaussian heat source, which accounted for the temperature de-pendence of thermal conductivity. Their model was generalized by a numerical algorithm set up by Moody and Hendel [11].…”
Section: Governing Equationmentioning
confidence: 99%